2017
DOI: 10.1111/sltb.12393
|View full text |Cite
|
Sign up to set email alerts
|

Personal Technology Use and Thwarted Belongingness Among Suicidal Active‐Duty Military Personnel

Abstract: This study (a) provides descriptive information about the personal technology use of a suicide sample of active-duty military personnel and (b) uses a traditional and a technology-based measure of social connectedness to examine their relation to suicide ideation and behaviors. Higher thwarted belongingness, and therefore lower perceived social connectedness, was associated with higher current and worst suicide ideation and a greater lifetime self-directed violence regardless of intent to die. Higher social co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Moreover, mixed findings are already available for newer technologies, illustrating that the influence of online interactions on TB is still unclear. While Moberg and Anestis [23] found that negative interactions on social networking sites predicted TB, Ringer and Anestis [12] only detected the independent associations of negative face-to-face interactions, but not of negative online interactions, with higher levels of TB, and Chalker and Comtois [24] did not find an association between TB and social connectedness via a mobile phone. Overall, these findings mainly suggest relations between TB and variables based on dysfunctional (interpersonal) cognitions (representing intrapersonal factors), while it remains rather unclear if there are also associations with more objective criteria, such as the mere presence of another person (representing interpersonal factors).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, mixed findings are already available for newer technologies, illustrating that the influence of online interactions on TB is still unclear. While Moberg and Anestis [23] found that negative interactions on social networking sites predicted TB, Ringer and Anestis [12] only detected the independent associations of negative face-to-face interactions, but not of negative online interactions, with higher levels of TB, and Chalker and Comtois [24] did not find an association between TB and social connectedness via a mobile phone. Overall, these findings mainly suggest relations between TB and variables based on dysfunctional (interpersonal) cognitions (representing intrapersonal factors), while it remains rather unclear if there are also associations with more objective criteria, such as the mere presence of another person (representing interpersonal factors).…”
Section: Introductionmentioning
confidence: 93%